Flexible, stretchable and conductive PVA/PEDOT:PSS composite hydrogels prepared by SIPN strategy. (January 2020) - Zhang, Yun-Fei; Guo, Ming-Ming; Zhang, Ya; Tang, Chak Yin; Jiang, Can; Dong, Yuqing; Law, Wing-Cheung; Du, Fei-Peng
Abstract: Stretchable conductive hydrogels have received significant attention due to their possibility of being utilized in wearable electronics and healthcare devices. In this work, a semi-interpenetrating polymer network (SIPN) strategy was employed to fabricate a set of flexible, stretchable and conductive composite hydrogels composed of polyvinyl alcohol (PVA) in the presence of glutaraldehyde as the crosslinker, HCl as the catalyst and poly(3, 4-ethylenedioxythiophene):polystyrenesulfonate (PEDOT:PSS) as the conductive medium. The results from FTIR, Raman, SEM and TGA indicate that a chemical crosslinking network and interactions of PVA and PEDOT:PSS exist in the SIPN hydrogels. The swelling ratio of hydrogels decreased with increasing content of PEDOT:PSS. Due to the chemical crosslinking network and interactions of PVA and PEDOT:PSS, PVA networks semi-interpenetrated with PEDOT:PSS exhibited excellent tensile and compression properties. The tensile strength and elongation at breakage of the composite hydrogels with 0.14 wt% PEDOT:PSS were 70 KPa and 239%, respectively. The compression stress of the composite hydrogels with 0.14 wt% PEDOT:PSS at a strain of 50% was about 216 KPa. The electrical conductivity of the hydrogels increased with increasing PEDOT:PSS content. The flexible, stretchable and conductive properties endow the composite hydrogel sensor with a superior gauge factor of up to 4.4 (strain: 100%). Coupling the strain sensing capability to the flexibility, good mechanical properties and high electrical conductivity, we consider that the designed PVA/PEDOT:PSS composite hydrogels have promising applications in wearable devices, such as flexible electronic skin and sensitive strain sensors. Highlights: A flexible, stretchable and conductive hydrogel is developed based on a semi-interpenetrating polymer network (SIPN) strategy. Chemically cross-linked PVA and linear PEDOT:PSS molecular chain organize the SIPN. The tensile strength and elongation at break of the composite hydrogels with 0.14 wt% PEDOT:PSS were 70 KPa and 239%, respectively. The electrical conductivity and strain sensitivity of hydrogels was increased with increasing the content of PEDOT:PSS. The PVA/PEDOT:PSS hydrogels demonstrated good flexibility, stretchability and strain-sensitivity, which has potential application in wearable electronics.